Comparison Between Conventional and Supersaturable Self-nanoemulsion Loaded with Nebivolol: Preparation and In-vitro/Ex-vivo Evaluation - Sabri, Lubna A.; A. Hussein, Ahmed (Iraqi Journal of Pharmaceutical Sciences, 2020)
Nebivolol (NBH) is a third-generation B1-blocker with high selectivity and vasodilation activity. Nevertheless, nebivolol exhibits low oral bioavailability, which may adversely affect its efficacy. Recently, supersaturable self-nanoemulsion (Su-SNE) is an advanced SNE approach that can address low bioavailability The study aims to prepare nebivolol-loaded Su-SNE by reduction the amount of the prepared conventional SNE to half. Besides, an appropriate polymer type and concentration to prevent NBH precipitation upon oral administration have investigated.. A conventional self-nanoemulsion (formula A) was prepared by dissolving NBH in 500 mg vehicle mixture of imwitor®988: cremophor-EL: propylene glycol. Then, eight Su-SNE formulas with the absence or presence of four different polymers were prepared and evaluated. In-vitro precipitation assay was performed to assess the precipitation inhibition capacity of polymers. The ex-vivo permeation through rat intestinal mucosa was also conducted for determination of permeability parameters. Results revealed that (Su-SNA formula SAS1) containing 5% soluplus could effectively retard the nebivolol precipitation. There was no statistical difference between formula A and SAS1; both maintained a higher apparent NBH concentration for approximately 240 min in 0.1N HCl. The permeation rate of conventional (formula A) and soluplus-based Su-SNE (formula SAS1) was significantly improved, and the permeation enhancement ratio was found 2.7 and 3.2, respectively, as compared with non-formulated NBH. Consequently, it is concluded that developing soluplus-based nebivolol SNE is a promising alternative approach. It can enhance nebivolol stability and permeability with half the amount of conventional SNE components.